Association between sarcopenia and sleep disorders: a cross-sectional population based study - Liu, Kepeng; Luo, Jinhui; Chen, Yong; Li, Binfei; Tian, Ye; Wang, Xianxue; Liao, Xiaozu (Frontiers in Nutrition, 2024)
Sleep disorders is a worldwide public health problem. We sought to examine the association between sarcopenia, a decline in skeletal muscle mass and function, and sleep disorders within the adult demographic of the United States during the period spanning 2011 to 2018.Diagnosis of sarcopenia and sleep disorders was ascertained through appropriate calculations and a structured questionnaire. The primary correlation analysis was conducted using a weighted multivariate logistic regression model. Furthermore, to confirm the presence of a potential nonlinear association between sarcopenia and sleep disorders, additional analyses were performed using multivariate logistic regression and restricted cubic spline (RCS) regression with dose-response curve analysis. Subgroup analyses were also conducted to explore the influence of relevant socio-demographic factors and other covariates.The final analysis encompassed 5,616 participants. Model 4, inclusive of all pertinent covariates, revealed a positive correlation between sarcopenia and sleep disorders, yielding an odds ratio (OR) of 1.732 (95% CI: 1.182-2.547; P = 0.002). Further analysis, utilizing the restricted cubic spline model, indicated a decreasing trend in sleep disorders as sarcopenia indices rose. Stratified analyses across diverse variables underscored the significant impact of sarcopenia on sleep disorders prevalence in several subgroups. Specifically, males, individuals aged 40 and above, non-Hispanic whites, those with high school education or equivalent, unmarried individuals, obese individuals (BMI ≥ 30), alcohol drinkers, former smokers, diabetics, and those engaging in less rigorous recreational activities exhibited a more pronounced association between sarcopenia and sleep disorders. The incidence of sleep disorders exhibited an upward trend as the incidence of sarcopenia declined among study participants.In summary, our study provides evidence of an association between sarcopenia and the prevalence of sleep disorders, with a negative correlation observed between the sarcopenia index and the odds ratio of sleep disorders. These findings suggest that maintaining optimal muscle mass may have a beneficial impact on sleep-related issues.In terms of exploring the mechanisms underlying the relationship between sarcopenia and sleep disorders, more in-depth research is warranted to ascertain the definitive causal relationship.